Isolation and identification of Aeromonas caviae from Eriocheir sinensis - XU Hai-sheng; HUANG Li-feng; WANG Shu xia (浙江大学学报. 农业与生命科学版)
Two strains of bacteria were isolated from haemolymph, liver, ascites and muscle of the diseased Eriocheir sinensis, which were cultured in the ponds in Zhuantang. Hangzhou. Both of the isolates were Gram-negative rods, motile by means of single polar flagella, and were facultatively anaerobic. Glucoce was catabolized with production of acid and no gas. Oxidase, Esculin, Catalase were positive, and nitrite was prodused from nitrate. Morpholohic, physiological and biochemical characteristics of the present isolates were the same as those of Aeromonas caviae, therefore, the pathogens isolated from the diseased Eriocheir sinensis were identified as Aeromonas cavwe. The mortality of artificial infection was 100%, which ascertained that the bacterial isolates were the pathogens of the Eriocheir sinensis. The pathogens were highly sensitive to streptomycin, kanamycin, neomycin, ciprofloxacin, norfloxacin. chloramphenical, gentamicin, tobramycin, ofloxacin, ceftazidime, cefuroxime, ceftriaxone. nalidixic acid, nitrofurantoin.